2016
DOI: 10.2147/opth.s109360
|View full text |Cite
|
Sign up to set email alerts
|

A comparison of patient pain and visual outcome using topical anesthesia versus regional anesthesia during cataract surgery

Abstract: PurposeThe purpose of this study was to compare the level of patient pain during the phacoemulsification and implantation of foldable intraocular lenses while under topical, intracameral, or sub-Tenon lidocaine.Patients and methodsThis was a retrospective study. Three hundred and one eyes subjected to cataract surgery were included in this study. All eyes underwent phacoemulsification surgery and intraocular lens implantation using topical, sub-Tenon, or intracameral anesthesia. The topical group received 4% l… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
5
0

Year Published

2017
2017
2023
2023

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 10 publications
(5 citation statements)
references
References 20 publications
0
5
0
Order By: Relevance
“…Given the advancements in equipment and the proficiency of surgical skills, topical anesthesia is the preferred method in phacoemulsification surgery to avoid the risks associated with local (retrobulbar or peribulbar) anesthesia, such as chemosis, ecchymosis, retrobulbar hemorrhage, globe penetration, or perforation; 1 , 2 however, phacoemulsification with topical anesthesia is not a completely painless procedure, with patients frequently experiencing pain during the surgery. 1 , 3 – 6 In a study comparing topical anesthesia and local anesthesia for phacoemulsification surgery, about 30.1% of patients with topical anesthesia complained of intraoperative pain, while only 6.7% of patients with local anesthesia reported intraoperative pain. 7 In another study, 78.3% of patients reported experiencing pain during phacoemulsification surgery with topical anesthesia; when the intensity of pain was evaluated, the percentage of patients reporting mild, moderate, and intense pain was 35.9%, 25.0%, and 17.4%, respectively.…”
Section: Introductionmentioning
confidence: 99%
“…Given the advancements in equipment and the proficiency of surgical skills, topical anesthesia is the preferred method in phacoemulsification surgery to avoid the risks associated with local (retrobulbar or peribulbar) anesthesia, such as chemosis, ecchymosis, retrobulbar hemorrhage, globe penetration, or perforation; 1 , 2 however, phacoemulsification with topical anesthesia is not a completely painless procedure, with patients frequently experiencing pain during the surgery. 1 , 3 – 6 In a study comparing topical anesthesia and local anesthesia for phacoemulsification surgery, about 30.1% of patients with topical anesthesia complained of intraoperative pain, while only 6.7% of patients with local anesthesia reported intraoperative pain. 7 In another study, 78.3% of patients reported experiencing pain during phacoemulsification surgery with topical anesthesia; when the intensity of pain was evaluated, the percentage of patients reporting mild, moderate, and intense pain was 35.9%, 25.0%, and 17.4%, respectively.…”
Section: Introductionmentioning
confidence: 99%
“…In addition, a particular attention should be paid to the patient's ability to communicate, to lie flat and keep still, and to follow instructions. A history of congestive heart failure, chronic obstructive pulmonary disease, chronic bronchitis, claustrophobia, anticoagulation status, and use of alpha-blockers (tamsulosin) should be addressed in each patient [35]. One should kept in mind that each technique has its own advantages and disadvantages, and the anesthesia provider should select the anesthesia technique Anesthetic agent is injected into the orbit, inside of the muscle cone.…”
Section: Conflict Of Interestmentioning
confidence: 99%
“…In a comparative study of topical, intracameral and sub-Tenon anesthesia, Hosada et al [27] 2016 reported that intracameral (0.1-0.2 cc) infusion of 1% preservative-free lidocaine into the anterior chamber through the side port combined with topical drops of lidocaine provides sufficient pain suppressive effects in eyes without high myopia, while sub-Tenon anesthesia is better for cataract surgery in eyes with high myopia. Pandey et al [28] reported no difference in pain score between with topical anaesthesia and no aneathesia during cataract surgery (p = 0.610) though patient discomfort and surgeon stress were greater in the no anesthesia group.…”
Section: Comparison Of Pain Scorementioning
confidence: 99%